Finite element analysis of non-uniform cross-section functionally graded coated beam subjected to mechanical loading - Toudehdehghan A.; Mathews J. (American Institute of Physics Inc., 2023)
The aim of this study is to show the advantage of Functionally Graded Material (FGM) as a coated layer and bond coated (under coated) layer in new coated beam structures. Three pattern coated such as Homogeneous Coated (HC), Functionally Graded Coated (FGC), and Homogeneous-Functionally Graded Coated (H-FGC) were considered. The static analysis of three different coated beam with non-uniform cross-section is emphasized for this study. The classical beam theory with several boundary conditions under uniformly transverse loading is analyzed by using Ansys software. In FGM layer of beams, changes of material properties are assumed based on layerwise method. The material properties in each layer differ as a sigmoid function along the thickness coordinate in order to analyze the composite. And also Poisson's ratio is considered constant across the thickness of coated beams. The deflections and stresses of coated beams are evaluated and under discussion based on two different material parameters. The results are showed that the H-FGC pattern has minimum deflection like the HC pattern. In the H-FGC pattern, the stress distribution at the interface of coated layer with substrate layer gradually change as well as the stress in the ceramic coated layer has not increased. 2019 Author(s).